Independent parallel pyrolysis kinetics of extracted proteins and lipids as well as model carbohydrates in microalgae. (15th October 2021) - Aniza, Ria; Chen, Wei-Hsin; Lin, Yu-Ying; Tran, Khanh-Quang; Chang, Jo-Shu; Lam, Su Shiung; Park, Young-Kwon; Kwon, Eilhann E.; Tabatabaei, Meisam
Graphical abstract: Highlights: Pyrolysis of protein, lipid, and carbohydrates from microalgae is investigated. The kinetics model gives a high fit quality for three pseudo-components. A synergistic effect is found in the thermodegradation of model carbohydrates. Glucose is the dominant species in the synergistic effect of carbohydrates. Four distinguished regions are discovered in the mixture of all the investigated constituents. Abstract: Microalgae offer unique potentials for developing advanced biorefineries, including third-generation biofuel production, wastewater treatment, and animal and aquaculture feed production. The thermodegradation of protein, lipid, and carbohydrates plays a vital role in the thermochemical conversion of microalgae for biofuel production. This work aims to investigate the kinetics and the interaction of extracted protein and lipid as well as model carbohydrates from microalgae to assist the development of microalgae conversion techniques, which have not been studied so far. Thermogravimetric analysis is integrated with an independent parallel reaction (IPR) and particle swarm optimization (PSO) method to explore the pyrolysis kinetics of three constituents (protein, lipid, and carbohydrates). The calorific values of the three constituents show that protein (5.33 MJ·kg −1 ) is not a suitable biofuel feedstock. In contrast, lipid (34.22 MJ·kg −1 ) and carbohydrates (15.37–15.84 MJ·kg −1 ) are considered as potential feedstocks for liquid and solid biofuel production, respectively. The pyrolysis processes suggest that the thermodegradation extent follows the order of carbohydrates > protein > lipid. The application of the IPR-PSO method on the pyrolysis kinetics of microalgae in three pseudo-components obtains a high fit quality (>96%) for all cases, indicating that the method is suitable to predict the kinetics parameters of the three constituents of microalgae. The effect analysis reveals that the synergistic effect accounts for about 50% of the total mass of the thermodegradation process of model carbohydrates, occuring at 200–320 °C. Meanwhile, the theoretical and experimental thermogravimetric analysis curve of combination of the three constituents suggests that there are four regions detected, including strong synergistic effect, weak antagonistic effect, weak synergistic effect, and strong antagonistic effect, respectively.